Evaluation of Post-Certification Teacher Competency Improvement Policies at Madrasah Aliyah Negeri Medan City - Juliani Juliani; Saiful Akhyar Lubis; Wahyudin Nur Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The aim of this research is to describe the evaluation of post-certification teacher competency improvement policies at Madrasah Aliyah Negeri Medan City. This research method is a qualitative research method with a phenomenological research approach. Collecting data using the method of observation, interviews, study documentation. The results of this study, namely (1) the policy context, such as competency training, educational qualifications, MGMP empowerment workshops and implementation of supervision. (2) Input, namely trying to become an institution that can help teachers sent by madrasas so that they have more ability in the 2013 Curriculum-based learning process. assignments in accordance with the demands of graduate competence, content, learning process, and 2013 curriculum assessment. (4) The product of the policy explains that the result is that the teacher has the ability to prepare syllabus, lesson plans, worksheets, teaching materials/materials, the media used in delivering material and the ability to compile an instrument for assessing student learning outcomes based on the 2013 Curriculum.